2021
DOI: 10.1097/cad.0000000000001221
|View full text |Cite
|
Sign up to set email alerts
|

Circular noncoding RNA circ_0007334 sequestrates miR-577 to derepress KLF12 and accelerate colorectal cancer progression

Abstract: Colorectal cancer (CRC) is a prevalent malignant tumor with a poor prognosis. Circular RNA (circRNA) circ_0007334 is related to cell proliferation in CRC. This study is designed to explore the role and mechanism of circ_0007334 in CRC progression. Circ_0007334, microRNA-577 (miR-577) and kruppel-like factor 12 (KLF12) levels were measured by real-time quantitative PCR (RT-qPCR). Exosomes were detected by a transmission electron microscope and nanoparticle tracking analysis (NTA). CD63, TSG101, matrix metallope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…In some cases, KLF12 was overexpressed and served as a tumor suppressor, for example, in bladder cancer ( Tang et al., 2021 ) and lung cancer ( Godin-Heymann et al., 2016 ). In other cases, KLF12 expression was correlated positively with disease severity such as in colorectal cancer ( Bai et al., 2021 ), lung cancer ( Mao et al., 2020 ), ovarian cancer ( Mak et al., 2017 ), and endometrial cancer ( Ding et al., 2019 ), indicating its tumor-promoting effect. In the present study, both the expressions of KLF12 in SiHa cells and tumor tissues based on the HPA database were significantly down-regulated compared with those in normal control cells or clinical samples.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, KLF12 was overexpressed and served as a tumor suppressor, for example, in bladder cancer ( Tang et al., 2021 ) and lung cancer ( Godin-Heymann et al., 2016 ). In other cases, KLF12 expression was correlated positively with disease severity such as in colorectal cancer ( Bai et al., 2021 ), lung cancer ( Mao et al., 2020 ), ovarian cancer ( Mak et al., 2017 ), and endometrial cancer ( Ding et al., 2019 ), indicating its tumor-promoting effect. In the present study, both the expressions of KLF12 in SiHa cells and tumor tissues based on the HPA database were significantly down-regulated compared with those in normal control cells or clinical samples.…”
Section: Discussionmentioning
confidence: 99%
“…22 And circ_0007334 deficiency restrained CRC cell growth, motility and angiogenesis via regulation of the miR-577/KLF12 axis. 23 However, the study about the function of circ_0003602 in CRC etiology is still restricted and requires further investigation. Previous research has reported that circ_0003602 was upregulated in acute myeloid leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…Circ 0007334 (Figure 7) was increased in CRC tissues and in CRC-derived exosomes (192). Knockdown of 0007334 impaired viability, colony formation, migration, invasion, angiogenesis, and tumor growth of CRC cells in vivo in immuno-deficient mice (193). Circ 0007334 sponged miR-577 resulting in up-regulation of KLF12 (193).…”
Section: Circular Rnas Up-regulating Transcription Factors and Rna-bi...mentioning
confidence: 99%
“…Knockdown of 0007334 impaired viability, colony formation, migration, invasion, angiogenesis, and tumor growth of CRC cells in vivo in immuno-deficient mice (193). Circ 0007334 sponged miR-577 resulting in up-regulation of KLF12 (193). The latter is part of the Krüppel-like factor family comprising 17 members with involvement in cell differentiation, proliferation, and apoptosis.…”
Section: Circular Rnas Up-regulating Transcription Factors and Rna-bi...mentioning
confidence: 99%